Problem-Based Learning Based on Coastal Abrasion Cases to Improve Conceptual Understanding and Problem-Solving Ability - Nur Fadilah; Suyitno Aloysius; Wahyudi Wahyudi (Jurnal Penelitian Pendidikan IPA, 2025)
Problem-solving ability is one of the higher-order thinking skills that students must possess, as it enables them to apply scientific knowledge to real-life situations. This study aimed to investigate the effect of problem-based learning (PBL), based on coastal abrasion cases, on improving students’ conceptual understanding and problem-solving ability. A quasi-experimental method with a pretest-posttest control group design was employed. The research was conducted in two classes: the experimental class used PBL, while the control class applied Discovery Learning. The sample consisted of 60 students. Instruments included tests designed to measure both conceptual understanding and problem-solving ability. Data were analysed using ANOVA. The results showed that the significance value was less than 0.05. This indicates that students who received PBL instruction achieved significantly higher scores in conceptual understanding and problem-solving ability than those taught using Discovery Learning. These findings suggest that PBL based on real-world issues, such as coastal abrasion, is effective in enhancing students’ scientific thinking and problem-solving skills